Sodium-Glucose Cotransporter-2 Inhibitor in Diabetic and Nondiabetic Renal Transplant Recipients - Lucie Maigret; Lucile Basle; Valérie Chatelet; Laure Ecotiere; Peggy Perrin; Léonard Golbin; Dominique Bertrand; Dany Anglicheau; Coralie Poulain; Cyril Garrouste; Clément Danthu; Charlotte Boud'hors; et al. (Kidney International Reports)
Introduction: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) improve cardiovascular prognosis in patients with chronic kidney disease (CKD), diabetes, and heart failure; and slow the decline of kidney dysfunction in patients with albuminuria. Although safety and efficacy of SGLT2i have not been investigated in kidney transplant recipients (KTRs), their marketing authorization leaves the possibility of their use in these patients in France. Methods: This was a prospective multicenter real-life study including all consecutive KTRs treated with SGLT2i. Results: We identified 347 KTRs treated with SGLT2i (97% with dapagliflozin), with an initiation of treatment most often beyond the first year after transplantation (87%). Importantly, 226 (65.1%) were diabetic and 245 (70.6%) were treated with angiotensin-converting enzyme (ACE) inhibitors or angiotensin-receptor blockers (ARBs). We found a low incidence of urinary tract infections (UTIs) (6.6%) and genital mycosis (0.6%), without any serious adverse event. Overall, SGLT2i were stopped in 54 patients (15.6%). The causes of SGLT2i discontinuations were very diverse. The main causes were graft dysfunction (32%), intercurrent infections (17%), urinary infections (11%), and digestive symptoms (9%). KTRs with a low estimated glomerular filtration rate (eGFR), especially those with eGFR < 30 ml/min per 1.73 m2, presented with the highest incidence of SGLT2i discontinuation (P = 0.003). SGLT2i were associated with a reduction in proteinuria, found in both diabetic and nondiabetic KTRs. In addition, they had an antihypertensive effect restricted to uncontrolled-hypertensive patients. Conclusion: SGLT2i have been used in KTRs since their authorization in France. They were discontinued more frequently in patients with impaired graft function; however, the expected side effects were infrequent and not life-threatening. The short-term antiproteinuric and antihypertensive effects are promising.